Effect of kinds of bio-fertilizers and organic and their interactions on the growth and yield of the Pistachio Cultivar Nab –IL Jamal (Damascus University Journal of agriculture sciences, 2021)
This research was carried out through the seasons 2018/2019 on Pistachio of Nab–Il Jamal cultivar, Cultivated in clay soils, in a private orchard in (Hama province). three types of organic and bio-fertilizers were used as (Trichoderma, Sheep manure, green manure, Interference between sheep manure and Trichoderma, and Interference between sheep manure and green manure) in addition to the control without fertilizers, to study their effects on the growth and yield of the Pistachios.The results showed that, the use of all fertilizers caused significant increase in studied indicators, and the best treatment was interference between sheep manure and Trichoderma, which achieved significantly the highest values, where average of leaf area was 21213 mm2, average length of parcels was 12.50 cm , average of length of shell was 20 mm, weight of the 100 shell was 132g and an annual yield was 30.33 kg/tree, compared with control, witch achieved (13459mm2, 7.5cm, 17mm,106.33g, 17.67kg) respectively.
Keywords: Pistachio, Nab –IL Jamal; Trichoderma; green manure; sheep manure; yield